Multikulturalisasi Pendidikan Islam Sejak Dini di Era Digital - Rahman, Mufiqur (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2018)
The failure to response digitalization evidenzed by the violence of child in the education institution and social environment that KPAI declared as the impact of digital culture and civilization that indicated instead of the failure of home’s education. This paper will discuss and share an idea with literature view methode with the urgent of multicultural Islamic education. The Values of Multiculturalsm can be tought early like humanity, tolerance, respecting minority, loving a weak, keeping unity and peace, mentaining the culture. Those values can be implemented by the following methode such as; 1. al-Awamiru wa an-Nawahy (order and forbid),. 2. Taqdimu al-Qudwah al-Toyyibah (modelling), 3. Al-Tsawabu wa al-I’qobu (reward and punishment). 4. Al-Iyha’u (direct method), . 5. Metode Qisshoh(story).